Case studies on diversity and social justice education - Gorski, Paul; Pothini, Seema G. (New York : Routledge, an imprint of Taylor & Francis Group, 2014)
'Case Studies on Diversity and Social Justice Education offers pre- and in-service educators an opportunity to analyze and reflect upon a variety of realistic case studies related to educational equity and social justice. Each case, written in an engaging, narrative style, presents a complex but common classroom scenario in which an inequity or injustice is in play. These cases allow educators to practice the process of considering a range of contextual factors, checking their own biases, and making immediate- and longer-term decisions about how to create and sustain equitable learning environments for all students.The book begins with a seven-point process for examining case studies. Largely lacking from existing case study collections, this framework guides readers through the process of identifying, examining, reflecting on, and taking concrete steps to resolve challenges related to diversity and equity in schools. The cases themselves present everyday examples of the ways in which racism, sexism, homophobia and heterosexism, class inequities, language bias, religious-based oppression, and other equity and diversity concerns affect students, teachers, families, and other members of our school communities. They involve classroom issues that are relevant to all grade levels and all content areas, allowing significant flexibility in how and with whom they are used. Although organized topically, the intersection of these issues are stressed throughout the cases, reflecting the multi-faceted way they play out in real life. All cases conclude with a series of questions to guide discussion and a section of facilitator notes, called points for consideration. This unique feature provides valuable insight for understanding the complexities of each case'--
Introduction: The case method ; The rest of this book -- Analyzing cases using the equity literacy framework: Equity literacy framework ; Case analysis : an equity literacy process ; A few final thoughts -- Cases on socioeconomic status: Chocolate bar fundraiser ; A class lesson in etiquette ; Student protest ; High expectations or unrealistic goals? -- Cases on religion: The winter party ; Christmas lights? ; A difference in perspectives ; Islamophobic read-aloud -- Cases on ethnicity and culture: Generalizations on display ; Not time for stories ; Inappropriate language ; Multicultural Day parade ; A place to study -- Cases on race: Task force ; Teaching race with Huckleberry Finn ; Diverse Friends Day ; Terms of endearment ; An uncomfortable field trip -- Cases on sex, gender, and gender identity: Boys versus girls trivia contest ; Gender bias with a smile ; Timmy's gender nonconformity ; Internet objectification -- Cases on (dis)ability ; A'surprise' fire drill ; Insufficient accommodations ; Nut allergy -- Cases on sexual orientation ; A new club ; Date auction ; Outed at school ; Two moms -- Cases on language: Student translator ; English only ; Family Night -- Cases on immigrant status: An assigned nickname ; I'm not black ; A legacy of privilege on the soccer field ; Parent involvement ; My uncle -- Appendix A: The equity literacy case analysis worksheet -- Appendix B: Points for consideration -- References.
Includes bibliographical references (pages 159-160).
Keywords: Multicultural education -- Case studies; Social justice -- Study and teaching